IoT smart laboratory system using node-red and raspberry PI - Carlos, Enseriban (2022)
The IOT (Internet of Things) technology is experiencing tremendous growth as the connectivity expands across the world, and it keeps on breaking the boundaries on showing what advanced technology can do. Most of the laboratories are lack of using IOT technology and still paying a high cost to ensure security. In the very common scenario, the appliances of the laboratory such as lights and air conditioners are kept left on, even when not in use. It leads to a rise in power consumption and wastage of energy in the laboratory. Therefore, this proposed project aims to develop a cost-effective and reliable IOT-based smart laboratory system that reduces power consumption and provides convenience for users to control laboratory appliances even at a distance. MQTT protocol is the communication between the server and client to publish and subscribe to the data. The ESP32s act as clients and the server acts as MQTT broker. This system utilizes Node MCU to connect several different sensors and transfer their data to the Raspberry Pi local server using Wi-Fi protocol, which will then send to the Digital Ocean cloud server. It enables users to stay connected with the laboratory from time to time by accessing the user-friendly interface website through smartphones or laptops. The real-time collected data will be displayed on the dashboard developed in Node-RED. The proposed smart laboratory system intends to efficiently control appliances using the Internet with the convenience of checking data from the website anytime, anywhere.